Smartphone-based ecological momentary assessment reveals mental health benefits of birdlife - Ryan Hammoud; Stefania Tognin; Lucie Burgess; Nicol Bergou; Michael Smythe; Johanna Gibbons; Neil Davidson; Alia Afifi; Ioannis Bakolis; Andrea Mechelli (Scientific Reports, 2022)
Abstract The mental health benefits of everyday encounters with birdlife for mental health are poorly understood. Previous studies have typically relied on retrospective questionnaires or artificial set-ups with little ecological validity. In the present study, we used the Urban Mind smartphone application to examine the impact of seeing or hearing birds on self-reported mental wellbeing in real-life contexts. A sample of 1292 participants completed a total of 26,856 ecological momentary assessments between April 2018 and October 2021. Everyday encounters with birdlife were associated with time-lasting improvements in mental wellbeing. These improvements were evident not only in healthy people but also in those with a diagnosis of depression, the most common mental illness across the world. These findings have potential implications for both environmental and wildlife protection and mental healthcare policies. Specific measures, aimed at preserving and increasing everyday encounters with birdlife in urban areas, should be implemented.